Back and Forth of Open Innovation: Outstanding Issues and Future Research Works - Budi, Andy Susilo Lukito (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2020)
This paper reviews the concept of open innovation compared to closed innovation. It starts with contrasting two papers about open innovation and discusses point of view from both papers and reveals outstanding issues from them. This paper continues with presenting issues about open innovation from various angles, such as classical organizational mechanism and theory, funding and commercialization, collaboration and intermediary agent role, as well as security and good governance conduct practice. Throughout the discussion process, it appeared some issues have been confirmed while some issues are still in large debate. This paper summarizes the unresolved issues into several potential research theme to be investigated further.Keywords: closed innovation, future research work, innovation topics, open innovation, open issues